2009
DOI: 10.1016/j.biopsych.2008.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Neurotransmitters Assessed by Proton Magnetic Resonance Spectroscopy: Relationship to Treatment Resistance in Major Depressive Disorder

Abstract: Background-Significant alterations in γ-aminobutyric acid (GABA) and glutamate levels have been previously reported in symptomatic and remitted major depressive disorder (MDD); however, no studies to date have investigated potential associations between these amino acid neurotransmitters and treatment-resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
167
5
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(189 citation statements)
references
References 39 publications
15
167
5
2
Order By: Relevance
“…Prior MRS studies revealed GABA reductions in depressed individuals compared with healthy controls, 11,28 with more pronounced MPFC reductions in a treatment-refractory subgroup. 15 Further, and also in support of the GABAdeficit hypothesis of depression, a variety of different antidepressants seem to function, in part, by elevating GABA. These include SSRIs, 12 the monoamine-oxidase inhibitor phenelzine, 29 the GABA-reuptake inhibitor tiagabine 30 and ECT.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Prior MRS studies revealed GABA reductions in depressed individuals compared with healthy controls, 11,28 with more pronounced MPFC reductions in a treatment-refractory subgroup. 15 Further, and also in support of the GABAdeficit hypothesis of depression, a variety of different antidepressants seem to function, in part, by elevating GABA. These include SSRIs, 12 the monoamine-oxidase inhibitor phenelzine, 29 the GABA-reuptake inhibitor tiagabine 30 and ECT.…”
Section: Discussionmentioning
confidence: 91%
“…Based on the majority of reports in patients with MDD on the neurochemical response to antidepressant therapy, 11,12,15 we hypothesized that TMS would selectively increase MPFC GABA levels while minimally affecting those of Glx.…”
Section: J Psychiatry Neurosci 2016;41(3)mentioning
confidence: 99%
“…Thus, weak inhibition, as may be found in depression, can prevent cortical plasticity (Fagiolini et al, 2004). In depression, in vivo magnetic resonance spectroscopy studies have found reduced cortical g-aminobutyric acid (GABA) concentrations (Sanacora et al, 1999;Price et al, 2009) with deficits in GABA receptor-mediated inhibition (Levinson et al, 2010). Further, there is evidence that the rate-limiting enzyme for GABA synthesis (GAD67) is reduced in the cortex of individuals with bipolar disorder (Thompson et al, 2009) and hippocampus of depressed individuals (Thompson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Proton magnetic resonance spectroscopy ( 1 H-MRS) is a safe, noninvasive method for repeated measure of brain GABA and glutamate in human subjects that does not require radioactive tracers or dyes. 1 H-MRS has been applied to the study of GABA and/or glutamate in seizure disorders (Petroff et al, 1995(Petroff et al, , 1996a, major depression (Price et al, 2009;Hasler et al, 2007;Sanacora et al, 1999Sanacora et al, , 2004Auer et al, 2000), anxiety disorders (Hasler et al, 2009;Goddard et al, 2001), premenstrual dysphoric disorder (Epperson et al, 2002), schizophrenia (Kegeles et al, 2012;Marsman et al, 2011), bipolar disorder (Benedetti et al, 2009), nicotine, alcohol, and cocaine addiction (Epperson et al, 2006;Gomez et al, 2011;Licata and Renshaw, 2010) and neurodegenerative diseases such as Parkinson's Disease and Alzheimer's Disease (Griffith et al, 2008). The majority of published in vivo human 1 H-MRS studies have been conducted at fields of 4 Tesla or less and have not included within day or between day reproducibility data for either GABA or glutamate.…”
Section: Introductionmentioning
confidence: 99%